Breakthrough or Breakaway Innovation? - Johnson, Walter G. (Science and Technology Law Review, 2026)
This article argues that expedited regulatory review programs for innovative products, like the Food and Drug Administration’s (FDA) Breakthrough Devices Program (BDP), should not be paired with immunity from tort liability for those products and their developers. Doing so both limits the ability of regulators to manage the risks of new products while simultaneously undermining incentives for their developers to adopt internal systems that address those risks. In non-emergency contexts, expedited review and liability immunity together could elevate innovation as a policy goal in the short-term above the more fundamental principles of safety and effectiveness for those new products over time and across populations. At minimum, if these two policies are deployed at once, they should only occur in the context of heightened regulatory supervision over those products both during and after review, backed up by a strong legal mandate for the regulator and adequate resources to conduct supervision. To make this argument, the article provides an in-depth analysis of the FDA’s Breakthrough Devices Program, an initiative from the 21st Century Cures Act for promoting innovation in medical devices by reducing scrutiny of their safety and effectiveness. The analysis applies doctrinal and empirical approaches to explore the Program’s legal foundations, current operations, and implications of liability preemption for patients and device manufacturers. Some patients have already been harmed by breakthrough devices and, while the Cures Act leaves some legal uncertainty, doctrinal analysis shows those patients appear likely to have limited remedies in tort law against some of these devices due to federal liability preemption. The article argues for loosening the current federal preemption of state-level tort liability for medical devices that were approved through the BDP, paired with greater regulatory supervision by the FDA both during and after the Program. While innovation remains an important policy goal, it should never surpass safety as a core regulatory imperative for novel products.